Research Performance Analysis of Five Key Parameters of Top 20 Indian Universities: An Evaluation - Mondal, Debdas (Journal of Data Science, Informetrics, and Citation Studies)
NIRF by the Ministry of Education, formerly MHRD ranks all these institutions, on five parameters, namely, (i) Metric for Quantitative Research (QNR), (ii) Metric for Qualitative Research (QLR), (iii) Metric for Students' & Faculty Contribution (SFC), (iv) Outreach & Inclusivity (OI), (v) Peer Perception (PR). The article reveals the evaluation information in the year 2021, the contributions of 20 highest Universities among 50 HEIs and their scores of parameters and sub-parameters under the “Research” category. It is a well-accepted fact that an increase in high-quality publications by a university would invariably result in the growth of its ranking. This study reflects that ranking has influenced the performance of universities positively. The study underscores that quality publications positively impacted rankings, highlighting the significance of research investment for overall university ranking enhancement. Furthermore, it found that the parameters set for assessing Indian institutions under NIRF align with those of other world university-ranking agencies. Universities scoring high for research productivity under NIRF also featured prominently in global rankings. Notably, universities from South India excelled in NIRF, indicating a close relationship between scholarly productivity and institutional ranking.
Keywords: National Institutional Ranking Framework; Research category; Top 20 universities; Research Performances of the parameters.